Pottery of Manqabad. - Incordino, Ilaria, (Access archaeology., 2023)
This volume presents, documents and analyses a new selection of ceramics from the Egyptian site of Manqabad (Asyut). It aims to present the most significant ceramic typologies from Manqabad, while collecting as many references and parallels as possible deriving from several different monastic sites in Egypt.